Organisational Culure and Academic Performance of Technical Management BSc Students - Kun, András István; Ujhelyi, Mária (International Journal of Engineering and Management Sciences, 2016)
Our study analyses the connection between perceived and ideal organizational cultures and academic results. A modified, self-managed OCAI questionnaire was used to measure perceived and ideal organizational cultures among engineering management students of the University of Debrecen Faculty of Engineering (N = 114). Our results reveal weak positive linear correlations between academic performance and perceived or ideal level of clan culture. In case of other culture types we did not find any consistent relationship. Based on our results students who consider clan culture ideal can expect better results than those who prefer other types. Among students who visit at least 61% of the classes those who reported fitting (or better fitting) perceived and ideal cultures tend to perform better in their studies.